Design thinking intervention in healthcare - ALSHEHRI, Mohammed Ali (Institutional Knowledge at Singapore Management University, 2020)
The healthcare industry is currently experiencing numerous challenges. Lack of skilled and innovative practitioners in healthcare organizations disrupts operational functions, administration, and service delivery. Dentistry is full of complex problems. There is currently a significant gap between the desired solutions dental providers offer to solve these problems and the actual outcomes. So, dental providers must rethink their approach to solving healthcare problems. One of the desirable approaches is design thinking. Application of design thinking in business and healthcare has demonstrated improved results. In this research, the objective was to investigate the application of design thinking in dentistry and its effects on patient experiences from staff and patient perspectives. Through design thinking, dental practitioners can develop new solutions to address the existing problems patients normally face, thus improving patient experiences. The research adopted a mixed method consisting of semi-structured interviews and surveys as well as an intervention. A design thinking workshop was carried out as an intervention to test the responses of the participants before and after the intervention. The workshop was administered in seven sessions. Staff responses were evaluated before and after the training sessions. Moreover, three days of training were conducted to educate the participants on using scripts and checklists in the workplace. The participant targeted in this research comprised of the staff and patients. The staff included dentists, dental assistants, receptionists, and administrators. The primary data collection tools included survey questionnaires and one-on-one semi-structured interview sessions. The main ethical issues for consideration are privacy, confidentiality, and informed consent. Design thinking was applied to solve complex dentistry problems, improve the outcomes for the staff, and improve patient experiences. The staff re-examined their dental practices and came up with new ways to handle dentistry problems and improve patient experiences. The findings indicated that there is no significant impact of design thinking methodology on empathy, and there is a significant impact of design thinking methodology on the other variables. We accepted the hypotheses that have a significant difference to improve the patient experience by design thinking intervention as well as staff attributes, physical facilities, and dentist initiative significantly increase patient satisfaction by design thinking intervention. Moreover, there were changes in staff responses before and after the workshop training sessions. The study is significant in providing insights into dental care practice improvements and advances the literature on design thinking and patient improvement in dental clinics.